Geometric Anisotropic Semivariogram Modelling of Hotspot Confidence Levels in South Matan Hilir Subdistrict - Gumilang, Ari Ratna; Vantika, Sandy (Jurnal Matematika, Statistika dan Komputasi, 2026)
The purpose of this research is to apply geometric anisotropic semivariogram modelling to confidence level of hotspots in South Matan Hilir Subdistrict, Ketapang Regency. The confidence level of hotspot can be used as an indicator of the likelihood of forest and land fires. A higher confidence level indicates a greater certainty that a fire has actually occurred at the hotspot location. The hotspot confidence level is spatial data because it is a random variable with an index location; therefore, the relationships among locations can be represented using a semivariogram model. A geometric anisotropic semivariogram model was employed in this study since the influence of direction exists in the distribution of hotspots. The results present that the exponential semivariogram model is the most suitable to represent the data, with the strongest spatial influence occurring in the north-south direction. Moreover, spatial dependence remains significant at a distance of 0.02027 .